Martinete Pilot Project: ¿Regeneration agent in Barrios Altos, Lima-Peru, 2002-2012? - Lopez Capa, Mishelle (2024)
The objectives of this research are to learn about the strategies proposed for the Martinete Pilot Project (MPP) and the indicators that influenced the non-compliance of the destugurization plan in its physical-spatial, social, management and/or administration, planning and its mechanisms, legal and financial devices, and inter-institutional cooperation dimensions, through the application of a qualitative methodology, explanatory level with a nonexperimental, longitudinal and analytical design, consisting of three stages of analysis.The main result is that the project in general has a medium and high performance, because, although it contributed with the urban renewal of the historic center and the destugurization, it did not go further due to the isolation it presents in relation to other neighboring communities. Finally, as a general conclusion, Barrios Altos is one of the most traditional neighborhoods with the presence of subdivided or abandoned plots, which showed intense processes of slum development due to overcrowding and urban social precariousness. Therefore, through the MPP, the public sector, the private sector, non-governmental organizations, as well as the beneficiary population itself, are the actors involved in reversing this situation.